2011
DOI: 10.1242/jeb.050062
|View full text |Cite
|
Sign up to set email alerts
|

Claudin 28b and F-actin are involved in rainbow trout gill pavement cell tight junction remodeling under osmotic stress

Abstract: SUMMARYPermeability of rainbow trout gill pavement cells cultured on permeable supports (single seeded inserts) changes upon exposure to freshwater or treatment with cortisol. The molecular components of this change are largely unknown, but tight junctions that regulate the paracellular pathway are prime candidates in this adaptational process. Using differential display polymerase chain reaction we found a set of 17 differentially regulated genes in trout pavement cells that had been exposed to freshwater api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Because changes in environmental conditions can be extremely varied, and diverse species of teleost fish cope with environmental change quite differently, the importance of cldns in the gill has already been addressed in a range of teleost species. These include broadly used model organisms such as zebrafish 53 and Tetraodon, 51 , 52 , 54 - 56 as well as other models such as Tetraodon biocellatus, 57 Salmo salar , 58 , 59 Oncorhynchus mykiss , 21 , 60 , 61 Fundulus heteroclitus , 62 Carassius auratus 21 , 23 and Paralichthys lethostigma 63 . When taking into account the aforementioned species and others, the number of cldns reported in gill tissue of teleost fishes is at least 44 (for review see ref.…”
Section: Tissue-specific Claudin Expression In Teleost Fishesmentioning
confidence: 99%
“…Because changes in environmental conditions can be extremely varied, and diverse species of teleost fish cope with environmental change quite differently, the importance of cldns in the gill has already been addressed in a range of teleost species. These include broadly used model organisms such as zebrafish 53 and Tetraodon, 51 , 52 , 54 - 56 as well as other models such as Tetraodon biocellatus, 57 Salmo salar , 58 , 59 Oncorhynchus mykiss , 21 , 60 , 61 Fundulus heteroclitus , 62 Carassius auratus 21 , 23 and Paralichthys lethostigma 63 . When taking into account the aforementioned species and others, the number of cldns reported in gill tissue of teleost fishes is at least 44 (for review see ref.…”
Section: Tissue-specific Claudin Expression In Teleost Fishesmentioning
confidence: 99%
“…In this regard, the bulk of work conducted thus far has focused on members of the claudin superfamily (e.g., Refs. 1,2,4,7,16,17,29,37,38,44,49,53,56). However, a number of studies have also revealed the potential importance of occludin (a member of the TAMP subfamily) in teleost fish gills (5,6,7,8,9,10,11,12,29).…”
mentioning
confidence: 99%
“…In 1983, Madara reported that apical hyperosmolality increases transepithelial electrical resistance (TER) and decreases cation selectivity concomitantly with an increase of TJ strands in guinea pig jejunum [5]. After that, however, there have not been many reports that studied the effects of osmolality on the paracellular transport [2633]. In addition, most of these reports showed that apical osmotic changes decreased TER but did not measure charge selectivity; therefore, the reduction in the barrier in these reports might result simply from disruption of cell-cell contacts.…”
Section: Discussionmentioning
confidence: 99%